The Impact of Different Muscle Relaxation Techniques on the Upper Trapezius and Its Relationship with the Middle Trapezius - Gao Li; Dan Liu; Di Yang; Ling He (Journal of Physiological Investigation)
The relaxation of trapezius muscles is widely believed to alleviate fatigue or injury of the trapezius muscles and reduce the risk of shoulder and neck pain. This study aims to examine the effects of different muscle relaxation techniques on the physical properties of the trapezius muscle and to explore how changes in the physical properties of the upper trapezius muscle affect those of the middle trapezius muscle. Twenty-four healthy males (mean age: 23.08 ± 0.97 years; height: 172.42 ± 4.61 cm; weight: 66.38 ± 6.68 kg; and body mass index: 22.30 ± 1.81 kg/m2), randomly divided into four groups: stretching relaxation group (ST, n = 6), mechanical vibration massage (MV, n = 6), pulse massage (PU, n = 6), and control (CO, n = 6). Measurements using the Myoton digital muscle assessment system were conducted daily over 2 weeks. The experimental groups demonstrated a notable decrease in tension and stiffness, accompanied by heightened elasticity in the upper trapezius muscles. Conversely, the control group exhibited contrasting trends. Although no significant variances were detected among the relaxation techniques, all proved efficacious compared to the control group (P < 0.05). Moreover, relaxation of the upper trapezius muscles significantly influenced the middle trapezius muscles (P < 0.05). Various relaxation methods positively influenced trapezius muscle attributes over 2 weeks, with inter-regional effects noted.